Laparoendoscopic single‐site (LESS) vs laparoscopic living‐donor nephrectomy: a systematic review and meta‐analysis. (15th July 2014) - Autorino, Riccardo; Brandao, Luis Felipe; Sankari, Bashir; Zargar, Homayoun; Laydner, Humberto; Akça, Oktay; De Sio, Marco; Mirone, Vincenzo; Chueh, Shih‐Chieh J.; Kaouk, Jihad H.
<x xml:space="preserve">Abstract</x> The aim of this study was to provide a systematic review and meta‐analysis of reports comparing laparoendoscopic single‐site (LESS) living‐donor nephrectomy (LDN) vs standard laparoscopic LDN (LLDN). A systematic review of the literature was performed in September 2013 using PubMed, Scopus, Ovid and The Cochrane library databases. Article selection proceeded according to the search strategy based on Preferred Reporting Items for Systematic Reviews and Meta‐analyses criteria. Weighted mean differences (WMDs) were used to measure continuous variables and odds ratios (ORs) to measure categorical ones. Nine publications meeting eligibility criteria were identified, including 461 LESS LDN and 1006 LLDN cases. There were more left‐side cases in the LESS LDN group (96.5% vs 88.6%, P < 0.001). Meta‐analysis of extractable data showed that LLDN had a shorter operative time (WMD 15.06 min, 95% confidence interval [CI] 4.9–25.1; P = 0.003), without a significant difference in warm ischaemia time (WMD 0.41 min, 95% CI –0.02 to 0.84; P = 0.06). Estimated blood loss was lower for LESS LDN (WMD −22.09 mL, 95% CI –29.5 to –14.6; P < 0.001); however, this difference was not clinically significant. There was a greater likelihood of conversion for LESS LDN (OR 13.21, 95% CI 4.65–37.53; P < 0.001). Hospital stay was similar (WMD –0.11 days, 95% CI –0.33 to 0.12; P = 0.35), as well as the visual analogue pain score at discharge (WMD –0.31, 95% CI –0.96 to 0.35; P = 0.36), but the analgesic requirement was lower for LESS LDN (WMD –2.58 mg, 95% CI –5.01 to –0.15; P = 0.04). Moreover, there was no difference in the postoperative complication rate (OR 1.00, 95% CI 0.65–1.54; P = 0.99). Renal function of the recipient, as based on creatinine levels at 1 month, showed similar outcomes between groups (WMD 0.10 mg/dL, –0.09 to 0.29; P = 0.29). In conclusion, LESS LDN represents an emerging option for living kidney donation. This procedure offers comparable surgical and early functional outcomes to the conventional LLDN, with a lower analgesic requirement. However, it is more technically challenging than LLDN, as shown by a greater likelihood of conversion. The role of LESS LDN remains to be defined.